Pendekatan politik Sultan Abu Al-Mahasin dan Sultan Mahmud Badaruddin II di Lampung pada abad XVII dan XIX M - Muhamad Alnoza (Berkala Arkeologi, 2021)
This study specifically aims to examine the power relations of the Sultan of Palembang (Sultan Mahmud Badaruddin II) in XIX century CE and the Sultan of Banten (Sultan Abu Al-Mahasin) in XVII century CE Lampung region based on piyagĕm Natayuda and dalung Bojong inscriptions. This study describes the form of political messages of Sultan Mahmud Badaruddin II and Sultan Abu Al-Mahasin in relation to the approach taken by the two kingdoms to the people of Lampung. Based on the analysis results of the inscriptions, it can be seen that the Sultanate of Palembang was more oriented towards a hard power approach, while the Sultanate of Banten was oriented to a combination of hard power and soft power.